Engagement with a formative assessment rubric: A case of mathematical reasoning. (2022) - Herbert, Sandra; Vale, Colleen; White, Pennie; Bragg, Leicha A.
Highlights: Mathematical reasoning is crucial for developing understanding in mathematics. Teachers struggle to identify students' mathematical reasoning. Assessment rubric assists in assessing students' mathematical reasoning. Assessment rubric assists in building teachers' knowledge of mathematical reasoning. Abstract: Mathematical reasoning is crucial for a deep understanding of mathematics, yet many primary teachers have a limited conception of reasoning. A deeper knowledge of reasoning is required to notice, teach, and assess it effectively. Sixteen pairs of teachers from four primary schools in Victoria, Australia, engaged in a professional learning program intended to assist teachers embed reasoning in their mathematics lessons. Transcripts of post lesson discussions were examined to investigate any changes in their knowledge of reasoning. Analysis indicates that most pairs demonstrated increased use of reasoning language. This study reveals the efficacy of assessing students' reasoning using the Assessing Mathematical Reasoning Rubric (AMRR) for building teachers' knowledge of reasoning. Examples of three pairs of teachers are provided to illustrate teachers' growing awareness of aspects of reasoning.